Medical missions in the Balkan wars through the prism of historical sources - Žikić, Milena; Arsić, Jasmina; Krajnović, Dušanka (Archives of Pharmacy, 2022)
In the first half of the 19th century, the Principality of Serbia began to work on developing the health service and educating medical staff by sending students abroad to study medicine, because there was no Medical Faculty. The aim of the paper is to present the participation of foreign medical missions in providing assistance to Serbia during the Balkan wars. Method of historical analysis by using the primary and the secondary data sources was applied. The new wave of war, which followed in the second decade of the 20th century, pointed to the lack of personnel, medical and pharmacy equipment. The lack of medical staff was compensated by medical missions from abroad. During the First Balkan War, Serbia was visited by 16 medical missions from all parts of Europe and Scandinavia with a total of 185 doctors. Only Russia sent eleven medical missions and thus took the leading position in providing assistance. The mission consisted of 28 doctors, 11 intendants, 2 pharmacists, 86 mercy nurses and 160 nurse assistants. In the Second Balkan War, England and Scotland, Denmark, Belgium, the Netherlands, Sweden, Norway, Germany, Russia, Hungary and Austria provided medical assistance with 85 doctors. All missions were consistent with love and dedication in saving lives, financing medical staff, medical supplies and hospital equipment. The courage and humanity of foreign missions was awarded the Order of Saint Sava.